Ultra-fast RP-HPLC-FD-DAD for quantification of total aflatoxins in maize, rice, wheat, peanut and poultry feed without sample clean up, and population exposure risk assessment in Katsina, Nigeria: an optimization study - Salisu, Baha'uddeen; Anua, Siti Marwanis; Wan Rosli, Wan Ishak; Mazlan, Nurzafirah; Haron, Rosliza (Journal of environmental science and health. Part B, Pesticides, food contaminants, and agricultural wastes, 2022)
This study reports the development and validation of a simple, yet efficient method called the ultra-fast reverse phase high-performance liquid chromatography with fluorescence and photodiode array detector (UF-RP-HPLC-FD-DAD) to extract and quantify the total aflatoxin from grains and poultry feed. The proposed method is used to determine the total aflatoxin content in 150 samples of maize, rice, wheat, peanut and poultry feed obtained from open markets in a state in Nigeria. The extent of consumer exposure to aflatoxins and the risk of developing hepatocellular carcinoma (HCC) are evaluated. The UF-RP-HPLC-FD-DAD method was found to be satisfactorily accurate, sensitive and reliable as ascertained by its excellent validation outcomes (R 2 > 0.999, LoD < 0.08 ng g −1 , LoQ < 0.2 ng g −1 , recovery = 90-102%). The aflatoxin levels in food grains and poultry feed samples obtained in this study implied a moderate dietary exposure of between 10.67 and 20.77 ng/kg BW/day, in which the risk of developing HCC was estimated to be between 6.27 and 21.40% per 100,000 adults/year. Hence, greater monitoring of marketed food and feed is required, besides the deployment of strict controls and preventive techniques to minimize the population's exposure to a high dietary level of aflatoxins.